Smear layer removal efficiency of Er,Cr;YSGG and Er:YAG lasers in root canals prepared with different NiTi File systems (Annals of Medical Research, 2021)
Aim: Evaluation of the root canal dentinal wall by scanning electron microscopy (SEM) in order to verify the presence/absence of smear layer after applying different NiTi file systems and Er:YAG and Er,Cr:YSGG lasers. Material and Methods: Hundred ninety-two mandibular incisors randomly divided into four groups (n=48). Each group was prepared with one of NiTi files: ProTaper Next, One Shape, Reciproc and Twisted file Adaptive using 5.25% NaOCl irrigation. Each group was then subdivided into four groups (n=12). Er,Cr:YSGG laser, Er:YAG laser and EDTA were separately applied to the first three subgroups. In the control group, no further disinfection protocol was performed. Then the roots were sectioned longitudinally and halves were examined under SEM. Results: Erbium laser systems removed the smear layer better than NaOCl irrigation, but not as much as EDTA/NaOCl. The greatest reduction in smear was obtained with Reciproc/EDTA and Reciproc/Er,Cr:YSGG groups. The success of irrigation protocols from highest to lowest was EDTA, ErCr: YSGG laser and Er:YAG laser.Conclusions: Single file NiTi instruments appeared to be more effective than multiple-file systems in leaving clean root canal walls. The reciprocating systems produced less smear layer than rotating instruments. Er:YAG and Er,Cr:YSGG laser activations appeared to be more efficient than syringe irrigation to remove the smear layer.Keywords: Er,Cr:YSGG laser; Er:YAG laser; NiTi file; SEM; smear layer.
Keywords: Er,Cr:YSGG laser; Er:YAG laser; NiTi file; SEM; smear layer.